2008
DOI: 10.1164/rccm.200703-373oc
|View full text |Cite
|
Sign up to set email alerts
|

IRF-1Gene Variations Influence IgE Regulation and Atopy

Abstract: Our results suggest that functionally relevant IRF-1 polymorphisms influence atopy risk, potentially by altering transcription factor binding, IRF-1 gene expression, and IFN-gamma regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…More importantly, we show that GRa is not required for CpdA-beneficial effects as previously thought. The observation that IRF-1 is increased in the airways of patients with asthma (50), combined with studies showing that polymorphisms in IRF-1 gene are associated with increased risk of childhood asthma (51) and with IgE regulation and atopy (52), strongly indicates that IRF-1 is a potential player in the pathogenesis of asthma. Our study shows that, in addition to directly impairing GC sensitivity (25), IRF-1 also regulates the expression of a number of GC-insensitive proasthmatic genes.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we show that GRa is not required for CpdA-beneficial effects as previously thought. The observation that IRF-1 is increased in the airways of patients with asthma (50), combined with studies showing that polymorphisms in IRF-1 gene are associated with increased risk of childhood asthma (51) and with IgE regulation and atopy (52), strongly indicates that IRF-1 is a potential player in the pathogenesis of asthma. Our study shows that, in addition to directly impairing GC sensitivity (25), IRF-1 also regulates the expression of a number of GC-insensitive proasthmatic genes.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the strong exposure of our asthmatic patients to mite allergens could modify the expected effects of the TGFB1 gene and its polymorphisms on IgE levels. This particular factor in the tropics, together with the genetic background of our population, allowed us to detect an association of the C-509 allele with higher levels of specific IgE to one of the most prevalent mites in house dust, adding TGFB1 to the increasing list of non-human leukocyte antigen genes influencing the specific immune response [28,43,64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…A previous report has provided evidence of NF-KB activity in nasal polyps specimen from AERD patients (Picado et al, 2003), while a conceptually similar finding has shown that accumulation of eosinophils in nasal polyp epithelium is mediated by NF-KB (Takeno et al, 2002). On the other hand, knockout mouse study reveals that IRF-1 deficiency results in elevated production of Th2-related cytokines in asthma (McElligott et al, 1997), and that IRF-1 polymorphisms affect regulation of IgE and the risk of atopy (Schedel et al, 2008), factors that have been identified as key mediators of asthma. The lack of previous functional reports demonstrating the exact molecular mechanisms of association does not exclude a possibility that FGD6 may induce AERD development either directly or via other functional elements mediated by the gene.…”
Section: Discussionmentioning
confidence: 95%